2020
DOI: 10.3389/fphar.2020.00712
|View full text |Cite
|
Sign up to set email alerts
|

Bakuchiol Attenuates Oxidative Stress and Neuron Damage by Regulating Trx1/TXNIP and the Phosphorylation of AMPK After Subarachnoid Hemorrhage in Mice

Abstract: Subarachnoid hemorrhage (SAH) is a fatal cerebrovascular condition with complex pathophysiology that reduces brain perfusion and causes cerebral functional impairments. An increasing number of studies indicate that early brain injury (EBI), which occurs within the first 72 h of SAH, plays a crucial role in the poor prognosis of SAH. Bakuchiol (Bak) has been demonstrated to have multiorgan protective effects owing to its antioxidative and anti-inflammatory properties. The present study was designed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 83 publications
(96 reference statements)
1
32
0
Order By: Relevance
“…GSH and SOD are among the most important physiological antioxidants against free radicals, preventing subsequent lipid peroxidation and protein oxidation [ 44 ]. When ROS and membrane lipids undergo lipid peroxidation reaction, a large quantity of lipid peroxidation products is produced, including MDA and 4-HNE, which are the markers that indicate the degree of lipid peroxidation [ 45 ]. ROS reacts with protein amino acid residues to produce protein oxidation products, among which 3-NT is a commonly used detection indicator [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSH and SOD are among the most important physiological antioxidants against free radicals, preventing subsequent lipid peroxidation and protein oxidation [ 44 ]. When ROS and membrane lipids undergo lipid peroxidation reaction, a large quantity of lipid peroxidation products is produced, including MDA and 4-HNE, which are the markers that indicate the degree of lipid peroxidation [ 45 ]. ROS reacts with protein amino acid residues to produce protein oxidation products, among which 3-NT is a commonly used detection indicator [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs, such as allopurinol and quercetin, have been found to prevent the overexpression of TXNIP in the rat liver and activation of the NLRP3 inflammasome, and upregulation of sterol-regulatory element–binding protein 1c (SREBP-1c), SREBP-2, liver X receptor α (LXRα), fatty acid synthase, and ROS while downregulating PPARα [ 146 ]. Moreover, several other small-molecule drugs, for example, telmisartan [ 172 ], bakuchiol [ 173 ], vorinostat (SAHA) [ 147 ], trichostatin A (TSA) [ 149 , 174 ], imatinib [ 150 ], taurine [ 151 ], and troglitazone [ 153 ] can inhibit the expression of TXNIP. Thielen L.A. et al recently identified a small-molecule inhibitor, SRI-37330, that effectively suppresses TXNIP expression in rats, mice, and human pancreatic islets.…”
Section: Txnip Is a Potential Therapeutic Targetmentioning
confidence: 99%
“…Trx‐1 may participate in NLRP6‐mediated signaling. The inhibition of the TXNIP expression through the activation of the AMPK pathway induces protective effects against diabetes following treatment with bakuchiol or sulforaphane, which induces the Trx protein (Groschwitz & Hogan, 2009 ; Han et al., 2016 ; Huang et al., 2015 ; Liu et al., 2020 ; Lv et al., 2020 ; Tanito et al., 2005 ). In addition, metformin, an oral antihyperglycemic agent, exerts a gastroprotective effect through increased mucus production, which is possibly related to the activation of the AMPK pathway (Noleto et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another natural compound, bakuchiol, exhibits multiorgan protective properties owing to its antioxidative and anti‐inflammatory activities. It exerts antidiabetic, antiaging, and anticancer effects by downregulating TXNIP protein levels, upregulating phosphorylation of AMPK, and increasing the levels of Trx‐1 protein and the tight junction protein, occluding, which regulates intestinal mucosal barrier function (Groschwitz & Hogan, 2009 ; Han et al., 2016 ; Huang et al., 2015 ; Liu et al., 2020 ). Moreover, metformin, which is known as an oral antihyperglycemic agent, has a gastroprotective effect that causes increased mucus production, possibly related to the activation of the AMPK pathway (Noleto et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%